Helical Computed Tomography Has a Role in the Screening of Lung Cancer -- The Con Argument - Warren Davidson (Canadian Respiratory Journal)
Screening constitutes the use of laboratory tests, physical examinations or imaging modalities performed on asymptomatic patients with the intent of identifying subclinical disease (1). As a result, screening differs from clinical investigation, in which tests are ordered after disease is suspected. A cancer screening program is a service in which everyone in a given population is (or has the opportunity to be) examined for the presence or precursor of a type of cancer. If the screening test finds that there is a likelihood of disease, a diagnostic test may be performed for confirmation (1).